L’area di Temesa tra confini geografici e interazioni culturali - Margherita Perri (Frontière·s)
Mentioned in the first book of the Odyssey as an emporium for the exchange of metals, Temesa is described as an eminent centre of the indigenous Italian world, to which the Greeks are attracted. According to Strabo, it was established by the Ausones and later conquered by the Aetolians, after the Trojan War. A few other literary sources report an intricate legend. It tells the story of one of Odysseus’s companions who came to Temesa, took advantage of the local hospitality and raped a young woman. As a result, he was killed by stoning and left unburied. He later turned into a demon, half man half wolf, and required the payment of a tribute. Temesa is freed from this curse by a boxer, Euthymos from Locri Epizefirî; this act marks the beginning of the settlement’s submission to Locri Epizefirî. This legend seems to be about the antagonism between indigenous communities and Greek navigators, as highlighted by the characters’ interactions and the story’s political conclusion. My archaeological investigation has found elements from the Middle Bronze Age onwards pertaining to this settlement, which fits into a geographical context specific to the Southern Tyrrhenian Coast. In its Archaic period, Temesa is at the crossroad of different cultures.